THE IMPLEMENTATION OF AUTOMATIC EXCHANGE OF INFORMATION AS A TOOL TO TACKLE OFFSHORE TAX EVASION: AN EXPERIENCE FROM INDONESIA - Darmanti, Riska Marlinda; Mangkan, Darmawan (Scientax, 2020)
Cross-border tax evasion has been a central issue in international taxation in recent years. The use of Offshore Financial Centres (OFCs) and low tax jurisdictions to facilitate the wealth of high net worth individuals has led to offshore tax evasion and has eroded the tax bases of countries. Meanwhile, international tax cooperation is emerging with the aim of enhancing tax transparency. One way to reach tax transparency is with the implementation of the exchange of information for tax purposes. The tax authorities have already implemented the exchange of information on request; however, this method is ineffective to fight against offshore tax evasion. The tax authorities must already obtain the evidence of their suspicion over the taxpayers; otherwise, their request may be denied as a ‘fishing expedition’. The demand for offshore financial information is obvious since it will enable tax authorities to oversee the level of offshore tax compliance. This study considers the importance of the Automatic Exchange of Information (AEOI) as a tool to access the resident’s financial information of residents who kept their financial assets in other jurisdictions with a case study in Indonesia. The financial information from other jurisdictions is fundamental for Indonesia because it can be used for analysis and law enforcement of taxpayers, especially those who previously saved money abroad and have not reported or paid the correct amount of tax. This paper recognizes that despite the benefits of the AEOI, the implementation of the AEOI in Indonesia is still facing challenges, although it has been two years since its first implementation. This study will follow a qualitative methodological approach with a detailed literature review and real experience in Indonesia. Finally, this article explores the current stage of implementing the AEOI in Indonesia and the challenges faced by Indonesia with some proposed solutions for the Directorate General of Taxes for the effective implementation of the AEOI in Indonesia.